Dual Antiplatelet Therapy Duration in Acute Coronary Syndrome Patients: The State of the Art and Open Issues. (7th April 2020) - Verdoia, Monica; Camaro, Cyril; Kedhi, Elvin; Marcolongo, Marco; Suryapranata, Harry; De Luca, Giuseppe
Abstract : Conflicting results have been reported so far in pooled analyses and studies evaluating the optimum duration of dual antiplatelet therapy (DAPT) in acute coronary syndrome (ACS) patients. However, randomized clinical trials dedicated to this specific setting of higher thrombotic risk patients have only recently been completed, pointing at the noninferiority of a shorter strategy as compared to the traditional 12-month DAPT, furthermore allowing to reduce the risk of major bleeding complications. Therefore, a reconsideration of current clinical practice and guidelines should be certainly be advocated in light of the most recent updates, especially among ACS patients treated with percutaneous coronary intervention (PCI) and modern drug-eluting stents (DES). Our aim was to provide a comprehensive review of the available evidence on the optimal DAPT duration in ACS patients.